Effective Ways to Inject Oil Revenues into the Economy in Oil Countries - Sadigov, Orkhan Tashakkul (International Journal of Energy Economics and Policy, 2020)
The main objective of the study is to explore how to achieve economic growth and the role of oil in the oil countries’ economy. The practical necessity of the article is to learn how to effectively integrate oil revenues into the country’s economy. At the same time, it is justified by the evidence that non-oil sector development and ultimately sustainable economic development can be achieved by injecting oil revenues into the economy efficiently and reasonably. Besides, at result of the study found that oil-rich countries for reaching long-term economic growth and sustainable economic development should be able to develop the non-oil sector and obtain economic diversification. Research work has been carried out on the basis of systematic analysis and methods. Scientific novelty of the research-modern features of oil revenues management and ways of its effective use were identified and in the result of research proposals were made. Keywords: diversification of the economy, non-oil sector development, oil revenues. JEL Classifications: E31, Q41, O11 DOI: https://doi.org/10.32479/ijeep.8921